Housing for Aboriginal Youth in the Inner City of Winnipeg - Brown, Jason; Knol, Dilly; Prevost-Derbecker, Sonia; Andrushko, Kelly (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2007)
Aboriginal families are highly overrepresented in child welfare caseloads. Major reasons for these high rates of involvement include poverty and housing issues, which contribute to perceptions of child neglect. In Winnipeg, the city with the highest proportion of Aboriginal peoples in Canada, low-cost housing is concentrated in core neighbourhoods. Homeless youth in these neighbourhoods, who are involved or have been involved in child welfare, were asked about their life experiences and the kind of housing that would help them. They talked about the need to be seen as resourceful, contributing members of the community, as well as their continued need of support from others, including friends and family. They wanted more than a place to sleep; they wanted a home that was safe, nurturing and long-term. The youth had school and work aspirations for themselves and wanted to help other youth reach their goals. There is a need for expansion of community-based and community-driven housing with youth who have been involved in the child welfare system.